Zambia – Beyond Connections : Energy Access Diagnostic Report Based on the Multi-Tier Framework - Luzi, Lucia; Lin, Yunhui; Koo, Brian Bonsuk; Rysankova, Dana; Portale, Elisa (World Bank, Washington, DC, 2019)
The Multi-Tier Framework (MTF) defines access to electricity according to a spectrum that ranges from Tier 0 (no access) to Tier 5 (full access) through seven attributes: Capacity, Availability,Reliability, Quality, Affordability, Formality, and Health and Safety. The final aggregate tierfor a given household is based on the lowest tier that that household attained among allthe attributes. The MTF survey data show that, as of 2017, 1.4 million Zambian households (42.4 percent) have access to electricity through either national grid or off-grid sources, while the remaining 1.9 million households (57.6 percent) have no access to electricity. Out of the 42.4 percent with electricity, most (37.7 percent of all households) are connected to the nationalgrid, and the remaining 4.7 percent primarily use off-grid solutions. The difference in access toelectricity between urban and rural areas is substantial: most urban households (74.8 percent)access electricity through the national grid, yet the majority of rural households (88.1 percent)have no access to any kind of electricity source. The MTF defines Tier 1 or above as havingaccess to electricity based on Sustainable Development Goal (SDG) 7.1.1. Nationwide, 40.3 percentof Zambian households are in Tier 1 or above for electricity access. Specifically, 75.2 percentof urban households and 8.7 percent of rural households are in Tier 1 or above. Grid users are mainly concentrated in Tiers 3 through 5, while user of off-grid solutions are primarily in Tiers 0 through 2. Nationwide, 59.7 percent of households are in Tier 0 for access to electricity, and the majority of them do not have any source of electricity. For households without any source of electricity, it will be critical to provide either an on-grid connection or an off-grid energy solution. Addressing high connection costs and offering flexible payment plans are likely to increase the grid-electrification rate. Grid infrastructure is available in 58.4 percent of the enumeration areas (EAs) in the country; however, only 37.7 percent of Zambian households are connected to the grid. The low uptake rate of grid connection opens up the possibility to increase grid electrification rate by around 20 percent through connecting households that are "under the grid," that is, directly beneath existing grid infrastructure. The penetration rate for off-grid solutions can also be improved by addressing Affordability issues through payment plans. Grid-connected households are mostly in higher tiers: 97.3 percent of grid-connected households are in Tier 3 or above, with 56.1 percent being in the highest tier, Tier 5. Challenges with Availability, Quality, and Reliability are the main issues preventing grid-connected households from being in the highest tier. Households using off-grid solar solutions are in Tiers 0 through 3, and they are mainly constrained by Capacity and Availability issues. Although the use of solar solutions is a relatively recent phenomenon in Zambia, 77.5 percent of solar users are satisfied with their current service from solar devices.